2004
DOI: 10.1136/gut.2002.012930
|View full text |Cite
|
Sign up to set email alerts
|

Gastric damage and granulocyte infiltration induced by indomethacin in tumour necrosis factor receptor 1 (TNF-R1) or inducible nitric oxide synthase (iNOS) deficient mice

Abstract: Background: Tumour necrosis factor a (TNF-a) is involved in non-steroidal anti-inflammatory drug induced gastropathy. Nitric oxide (NO) is a mediator of gastrointestinal mucosal defence but, paradoxically, it also contributes to mucosal damage. Aims: We optimised the C57BL/6 mouse model of indomethacin induced gastropathy to evaluate the role of TNF-a and inducible nitric oxide synthase (iNOS) generated NO in gastric damage and granulocyte infiltration using tumour necrosis factor receptor 1 (TNF-R12/2) or iNO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
54
2
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(62 citation statements)
references
References 36 publications
4
54
2
2
Order By: Relevance
“…However, even after 7 days, the autohealing was partial. The MPO activity, a marker of neutrophil aggregation at the site of inflammation frequently increases in ulcerated condition and reduces with the healing process (Souza et al, 2004). In consonance with this, we also found that ulceration increased the MPO activity up to the 4th day, followed by its gradual reduction on the 7th day (Fig.…”
Section: Discussionsupporting
confidence: 73%
“…However, even after 7 days, the autohealing was partial. The MPO activity, a marker of neutrophil aggregation at the site of inflammation frequently increases in ulcerated condition and reduces with the healing process (Souza et al, 2004). In consonance with this, we also found that ulceration increased the MPO activity up to the 4th day, followed by its gradual reduction on the 7th day (Fig.…”
Section: Discussionsupporting
confidence: 73%
“…Several studies have demonstrated the importance of endogenous NO in the protection of gastric mucosa (Kim and Kim, 1998;Tanaka et al, 2001;Whittle et al, 1990). Also endothelial NO plays an important role in the modulation of gastric mucosal integrity by interacting with sensory neuropeptides (Whittle et al, 1990;Tepperman and Whittle, 1992), reducing neutrophil adhesion and increasing gastric blood flow and mucus secretion (Souza et al, 2004). In the present study, alcohol significantly reduced gastric mucosal NO level with increase mucosal injury compared to control group.…”
Section: Discussionsupporting
confidence: 54%
“…Mucosal blood flow is essential to maintain gastric mucosal integrity; hence increased blood flow would reduce the risk of lesion by NSAID treatment. Thus, an increase in gastric blood flow resulting from H 2 S donation could primarily prevent any initial mucosal lesion by reducing the production of local inflammatory mediators, consequently reducing leukocyte to endothelium adhesion, an event essential to the progression of gastric tissue lesion (46). Reinforcing this explanation, NO synthase inhibitors that improve neutrophil migration induced by different stimuli (27) have been shown to enhanced the NSAID-induced gastric lesion via a reduction of mucosal blood flow (47,48).…”
Section: Discussionmentioning
confidence: 87%